Distinct protein signature of hypertension-induced damage in the renal proteome of the two-kidney, one-clip rat model. Issue 1 (January 2015) - Vethe, Heidrun; Finne, Kenneth; Skogstrand, Trude; Vaudel, Marc; Vikse, Bjørn E.; Hultström, Michael; Placier, Sandrine; Scherer, Andreas; Tenstad, Olav; Marti, Hans-Peter
<x xml:space="preserve">Abstract</x> Background: Hypertensive nephrosclerosis is one of the most frequent causes of chronic kidney failure. Proteome analysis potentially improves the pathophysiological understanding and diagnostic precision of this disorder. In the present exploratory study, we investigated experimental nephrosclerosis in the two-kidney, one-clip (2K1C) hypertensive rat model. Methods: The renal cortex proteome from juxtamedullary cortex and outer cortex of 2K1C male Wistar–Hannover rats (n = 4) was compared with the sham-operated controls (n = 6), using mass spectrometry-based quantitative proteomics. We combined a high abundant plasma protein depletion strategy with an extended liquid chromatographic gradient to improve peptide and protein identification. Immunohistology was used for independent confirmation of abundance. Results: We identified 1724 proteins, of which 1434 were quantified with at least two unique peptides. Comparative proteomics revealed 608 proteins, including the platelet-derived growth factor receptor-β signalling pathway, with different abundances between the non-clipped kidney of hypertensive 2K1C rats and the corresponding kidney of the normotensive controls (P < 0.05, absolute fold change ≥1.5). Among the most significantly altered proteins in the whole cortex were periostin, transgelin, and creatine kinase B-type. Relative abundance of periostin alone allowed clear classification of 2K1C and controls. Enrichment of periostin in 2K1C rats was verified by immunohistology, showing positivity especially around the fibrotic vessels. Conclusion: The proteome is altered in hypertension-induced kidney damage. We propose periostin, especially in combination with transgelin and creatine kinase B-type, as possible proteomic classifier to distinguish hypertensive nephrosclerosis from the normal tissue. This classifier needs to be further validated with respect to early diagnosis of fibrosis, prognosis, and its potential as a novel molecular target for pharmacological interventions.